Variables and Assumptions in Modern Interpretation of Ancient Spinning Technique and Technology Through Archaeological Experimentation - Tracy P. Hudson (EXARC Journal, 2014)
This paper takes the form of a critical analysis of archaeological experiments using spinning tools. The archaeological experiments regarding whorl weight and wool spinning of the Tools and Textiles – Texts and Contexts project, through the Danish National Research Foundation’s Centre for Textile Research, are examined with respect to a number of variables. These variables include the experience of the technicians, the details of the reconstructed spindles and technical aspects of preparation and spinning methods. The variables and their implications are insufficiently addressed in the technical reports of the experiments, and further consideration and elucidation would enhance the interpretation of experimental results. Archaeological experimentation of this type would also benefit from the incorporation of ethnographic observation to provide contextual information and comparative behavioural data. The assumptions inherent in modern approaches to fibre technology and their influence on archaeological experimentation are considered, with a view toward encouraging a more self-conscious approach to the analysis of fibre experiments.